Targeting Bruton’s Tyrosine Kinase in Inflammatory and Autoimmune Pathologies - Neys, Stefan F. H.; Hendriks, Rudi W.; Corneth, Odilia B. J. (Frontiers in Cell and Developmental Biology, 2021)
Bruton’s tyrosine kinase (BTK) was discovered due to its importance in B cell development and has a critical role in signal transduction downstream of the B cell receptor (BCR). Targeting of BTK with small molecule inhibitors has proven to be efficacious in several B cell malignancies. Interestingly, recent studies revealed increased BTK protein expression in circulating resting B cells of patients with systemic autoimmune disease compared to healthy controls. Moreover, BTK phosphorylation following BCR stimulation in vitro was enhanced. In addition to its role in BCR signaling, BTK is involved in many other pathways, including pattern recognition, Fc, and chemokine receptor signaling in B cells and myeloid cells. This broad involvement in several immunological pathways provides a rationale for the targeting of BTK in the context of inflammatory and systemic autoimmune disease. Accordingly, numerous in vitro and in vivo pre-clinical studies support the potential of BTK targeting in these conditions. Efficacy of BTK inhibitors in various inflammatory and autoimmune diseases has been demonstrated or is currently evaluated in clinical trials. In addition, very recent reports suggest that BTK inhibition may be effective as immunosuppressive therapy to diminish pulmonary hyperinflammation in coronavirus disease 2019 (COVID-19). Here, we review BTK’s function in key signaling pathways in B cells and myeloid cells. Further, we discuss recent advances in targeting BTK in inflammatory and autoimmune pathologies.